Binocular rivalry in children with schizophrenia: the conscious and unconscious cognitive processing of interpersonal information - Wang, Meijuan (Editorial Department of the Shanghai Archives of Psychiatry, 2013)
BACKGROUND: Childhood schizophrenia is a severe mental disorder that is believed to affect both conscious and unconscious cognitive functioning, but there have been few studies that have assessed this. OBJECTIVE: Develop a version of the binocular rivalry test that will assess the conscious and unconscious cognitive processing of interpersonal information and use this test to determine whether or not social cognition is impaired in children with schizophrenia. METHODS: Thirty images of three types – with no persons, with 2-3 persons and with 4+ persons – were selected for use in a binocular rivalry test that presented the images both in an interocularly suppressed (unconscious) format and an unsuppressed (conscious) format. Fifteen children under 16 years of age with schizophrenia who had prominent delusional symptoms and 15 healthy children were administered the test. Accuracy rates (in assessing the left or right orientation of a patch presented immediately after the target images) and reaction times were compared between patients and controls. RESULTS: For all types of pictures, the accuracy of patients was less than that of controls, though the differences were only significant in two of the twelve comparisons assessed. Compared to controls, patients showed a non-significant increase in the attention paid to images with people in them compared to images without people in them, both for conscious and unconscious presentations of the images. We did not find any relationship between the severity of psychotic symptoms in the patients and the degree of impairment in the cognitive processing of images. When asked to assess the attributes of the images, patients reported significantly higher levels of happiness depicted in images with 2-3 people than controls. CONCLUSIONS: The non-significant increase in the attention children with schizophrenia paid to images depicting interpersonal relationships suggests, but does not prove, that the illness is associated with impairments in the cognitive processing of social information. Our use of the binocular rivalry paradigm to identify these differences was only partially successful, largely because of the wide variability in the key index from the test used to assess the amount of attention respondents pay to different types of images.